2017
DOI: 10.1002/cpt.606
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Kidney Injury Biomarkers in Patients Receiving Cisplatin: Time‐dependent Changes in the Absence of Clinical Nephrotoxicity

Abstract: The success of cisplatin-containing regimens to treat solid tumors is limited, in part, by nephrotoxicity. In rodents, several urinary proteins have emerged as more sensitive indicators of cisplatin-induced kidney injury. We sought to characterize time-dependent changes in the urinary concentrations of 12 proteins including KIM-1, calbindin, β2M, and TFF3 after cisplatin therapy. Urine was collected at baseline, 3 (range: 2-5), and 10 (range: 9-11) days from 57 patients with solid tumors receiving outpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 47 publications
0
50
0
6
Order By: Relevance
“…There have been several reports suggesting that uB2MG concentrations elevated three folds by day 3 of UTI, whereas NGAL levels increased earlier (12 hours to 3 days). 31) …”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports suggesting that uB2MG concentrations elevated three folds by day 3 of UTI, whereas NGAL levels increased earlier (12 hours to 3 days). 31) …”
Section: Discussionmentioning
confidence: 99%
“…The eGFR was obtained from the medical record at baseline and after the first cisplatin dose and calculated using the CKD-EPI equation [ 33 ]. Additional details on biomarker analysis methods was previously published [ 57 ]. Biomarker data was not normalized to urinary creatinine as our previous study demonstrated similar findings with absolute and normalized data [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additional details on biomarker analysis methods was previously published [ 57 ]. Biomarker data was not normalized to urinary creatinine as our previous study demonstrated similar findings with absolute and normalized data [ 57 ]. Biomarker data was assayed at baseline, and Day 3 and Day 10 post cisplatin administration.…”
Section: Methodsmentioning
confidence: 99%
“…The power of these and other biomarkers to detect subtle renal injury has been well illustrated with cisplatin …”
Section: Today and The Near Termmentioning
confidence: 99%